Analysis of the Effects of Financial Inclusion and Peer-to-Peer (P2P) FinTech Lending on Economic Growth in Indonesia - Maghfiroh, Ramadhani Rohmatul; Tyas Danarti Hascaryani (Contemporary Studies in Economic, Finance and Banking, 2025)
The financial sector plays a crucial role in the economy, leading many countries to utilize the level of financial inclusion as a key indicator of success in achieving long-term economic growth. Furthermore, the emergence of Peer-to-Peer (P2P) lending FinTech in the digital era is widely considered to have the potential to address the financial access gap left by traditional financial institutions. However, empirical studies investigating the influence of P2P lending FinTech on economic growth, particularly in Indonesia, remain very limited. The objective of this study is to examine the impact of financial inclusion and FinTech P2P lending on economic growth in Indonesia. Employing a quantitative approach, this research utilizes panel data regression with the Fixed Effect Model (FEM), drawing on panel observations from 33 provinces over the period 2019–2024. The results of the study indicate that the proxy for financial inclusion based on the number of bank branches (access) has a negative and statistically significant effect on economic growth. Conversely, the proxy for financial inclusion based on the amount of bank credit disbursement (usage), along with FinTech P2P lending, both exhibit a positive and statistically significant effect on economic growth.